2011
DOI: 10.1088/0004-637x/742/2/109
|View full text |Cite
|
Sign up to set email alerts
|

37 GHz METHANOL MASERS : HORSEMEN OF THE APOCALYPSE FOR THE CLASS II METHANOL MASER PHASE?

Abstract: We report the results of a search for class II methanol masers at 37.7, 38.3 and 38.5 GHz towards a sample of 70 high-mass star formation regions. We primarily searched towards regions known to show emission either from the 107 GHz class II methanol maser transition, or from the 6.035 GHz excited OH transition. We detected maser emission from 13 sources in the 37.7 GHz transition, eight of these being new detections. We detected maser emission from three sources in the 38 GHz transitions, one of which is a ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
94
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(108 citation statements)
references
References 57 publications
12
94
2
Order By: Relevance
“…The line of best fit for the full sample and those sources associated with excited-state OH masers have the same slope within the errors (0.84 ± 0.03 and 0.91 ± 0.13 for the full sample and excited-state OH-associated sample, respectively). In similar comparisons, Ellingsen et al (2011) and Breen et al (2012b) found that rarer methanol maser transitions (at 107-and 37.7-GHz) Figure 7. Peak luminosity of the 12.2-GHz maser emission versus the peak luminosity of the 6.7-GHz maser emission (units of Jy kpc 2 ) for 12.2-GHz methanol masers detected in the longitude range 186 • (through the Galactic Centre) to 60 • (Breen et al 2012a(Breen et al ,b, 2014, plus the current paper; black dots).…”
Section: Associations With Excited-state Oh Masersmentioning
confidence: 56%
“…The line of best fit for the full sample and those sources associated with excited-state OH masers have the same slope within the errors (0.84 ± 0.03 and 0.91 ± 0.13 for the full sample and excited-state OH-associated sample, respectively). In similar comparisons, Ellingsen et al (2011) and Breen et al (2012b) found that rarer methanol maser transitions (at 107-and 37.7-GHz) Figure 7. Peak luminosity of the 12.2-GHz maser emission versus the peak luminosity of the 6.7-GHz maser emission (units of Jy kpc 2 ) for 12.2-GHz methanol masers detected in the longitude range 186 • (through the Galactic Centre) to 60 • (Breen et al 2012a(Breen et al ,b, 2014, plus the current paper; black dots).…”
Section: Associations With Excited-state Oh Masersmentioning
confidence: 56%
“…Other, rarer, maser transitions also have a special role to play -signposting physical conditions that Email: Shari.Breen@sydney.edu.au are less commonly found, or, perhaps more likely, associated with short-lived evolutionary phases in the star formation process (e.g. Ellingsen et al 2011Ellingsen et al , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of methanol and water masers have further refined and quantified the maser-based timeline (e.g. Breen et al 2010aBreen et al , 2010bEllingsen et al 2011). The sensitive GASKAP study represents a unique opportunity to robustly test and refine the way that ground-state OH maser emission fits in the timeline.…”
Section: Dickey Et Almentioning
confidence: 99%